Fine Motor Development in Early Childhood - Aidil Putra; Ela Dian Pintari (Universitas Negeri Padang, 2019)
This study aims to develop fine motor skills in early childhood through the provision of appropriate stimulation. In addition, this study was conducted in order to find out how much influence the activities of writing and drawing in children aged 4-5 years. Fine motor skills themselves are physical movement abilities that involve small muscles in the child such as grasping, pinching, squeezing, etc. It is very important to be able to provide stimulation in the development of fine motor skills of children so that their motor skills are not impeded. Fine motor skills in early childhood can be developed by inviting children to write, doodle, and draw and other activities that involve small muscle movements. Data collection was carried out by conducting research on 2 children who have the same age ratio of 5 years, this study was conducted by the method of observation. Provision of stimulation through writing, crossing out, and drawing activities are proven to help the development of fine motoric children where when children hold a pencil, the child initially seems unwilling and stiff but over time the child becomes stimulated to continue to do so.Keywords: Fine Motor, Writing and Drawing